Neuromyotonia in hereditary motor neuropathy. - Hahn, A F (1991)
Two siblings with a distal motor neuropathy experienced cramping and difficulty in relaxing their muscles after voluntary contraction. Electromyographic recordings at rest revealed repetitive high voltage spontaneous electrical discharges that were accentuated after voluntary contraction and during ischaemia. Regional neuromuscular blockage with curare indicated hyperexcitability of peripheral nerve fibres and nerve block suggested that the ectopic activity originated in proximal segments of the nerve. Symptoms were improved with diphenylhydantoin, carbamazepine and tocainide.